Whole-grain intake, incident hip fracture, and presumed frailty in the Iowa Women’s Health Study - Jacobs, David R. (2010)
Whole cereal grain foods are high in phytate, a calcium chelator, and could increase risk of hip fracture. We investigated baseline whole grain intake and incident hip fracture. We followed 29,192 women who, at baseline in 1986 were aged 55–69 y, free of diabetes, reported plausible energy intake of 600–5000 kcal/d, and reported no fracture since age 35 y. Hip fracture (n=746) was self-reported in 5 questionnaires through 2004. Of 1451 hip fractures identified passively by Medicare linkage through Dec 31, 2004 (Medicare hip fracture), 507 had also been self-reported. Whole grain intake was inversely related to Medicare hip fracture (p(trend)=0.02), but was unrelated to self-reported hip fracture (p(trend)=0.27). The hazard ratio in highest to lowest quintile of whole grain intake for incident Medicare only hip fracture (n=944) was 0.68 (95% confidence interval 0.56, 0.84) after adjustment for age, energy intake, education, body mass index, waist to hip ratio, farm residence, physical activity, estrogen use, smoking, alcohol use, history of cancer and other dietary variables. Medicare only cases may have failed to self-report due to severe illness; hazard ratio for total mortality after hip fracture was 2.92 (2.37,3.59) for Medicare only cases vs Medicare-confirmed self-reported cases. In conclusion, in this cohort, an inverse association of whole grain intake with hip fracture was explained by ascertainment bias. Whole grain intake may increase ability to respond to a questionnaire and self-report hip fracture and could reflect less undocumented frailty.